Catastrophic floodings, bursting and transit freshets under the conditions Caucasus and daghestan fnd recommendations on their preventing - V. Sh. Scomoya; H. A. Ahmedrabadanova; E. R. Katiashvili (Юг России: экология, развитие, 2015)
There are given the results of calculating of maximum coasumplion of water of flooding, bursting and transit frishets and new materials about Daghestan. There are getting the good results and the deflecting from actual facts doesЃЊT exeed 5-7%.